Sperm kinetics of Egyptian buffalo bulls (Bubalus bubalis) affected by the red laser postfreezing - Dessouki, Sherif Mohamed; Ahmed, Dalia Abd El Rahman; Fayed, Ayat Kassem (Journal of Advanced Veterinary and Animal Research, 2022)
Objective: To improve the fertilizing ability of frozen buffalo semen using the more beneficial, accurate, and cheap technique of laser irradiation at specific wavelengths and exposure times. Materials and Methods: The red laser source (625 nm) was used in this study with 5 watts output power and for the irradiation of the semen samples for 5 min; the laser focus spot area was 1 cm2. Thirty straws belonging to five buffalo bulls were used in this study. Results: The results show that total motility (%) and progressive motility (%) increased insignificantly after 5 min of exposure (73.8 ± 1.4 and 60.4 ± 1.1, respectively) compared to the control sample (70.9 ± 0.9 and 57.5 ± 1.7, respectively). All velocity parameters (velocity average path, velocity curved line, and velocity straight line µm/sec) recorded a significant (p < 0.05) increase in samples measured 5 min after exposure (52.3 ± 1.3, 83.5 ± 2.0, and 43.5 ± 1.2, respectively) compared to the untreated ones (47.1 ± 2.0, 76.3 ± 3.1, and 38.6 ± 1.9, respectively). Conclusion: The application of the red laser light on buffalo semen postthawing resulted in a positive correlation with almost every motility parameter; it may be recommended to apply this technique pre-in vitro fertilization for embryo production of buffalo species. J. Adv. Vet. Anim. Res., 9(3): 396–404, September 2022 http://doi.org/10.5455/javar.2022.i607